2015
DOI: 10.1080/15226514.2014.981246
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Heavy Metals in Mining Affected Soil and Their Bioaccumulation in Native Plant Species

Abstract: Several anthropogenic and natural sources are considered as the primary sources of toxic metals in the environment. The current study investigates the level of heavy metals contamination in the flora associated with serpentine soil along the Mafic and Ultramafic rocks northern-Pakistan. Soil and wild native plant species were collected from chromites mining affected areas and analyzed for heavy metals (Cr, Ni, Fe, Mn, Co, Cu and Zn) using atomic absorption spectrometer (AAS-PEA-700). The heavy metal concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(24 citation statements)
references
References 49 publications
(45 reference statements)
2
21
0
1
Order By: Relevance
“…Another concern regarding the safe use of organic fertilizers in agriculture is the possible presence of heavy metals that have a negative impact on the environment. Heavy metals can accumulate in agricultural soils, leach into soil solution and reach the groundwater and, in the long term, they may contaminate both human and animal food chain (Nawab et al 2015;Rahman et al 2014;Singh and Kalamdhad 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Another concern regarding the safe use of organic fertilizers in agriculture is the possible presence of heavy metals that have a negative impact on the environment. Heavy metals can accumulate in agricultural soils, leach into soil solution and reach the groundwater and, in the long term, they may contaminate both human and animal food chain (Nawab et al 2015;Rahman et al 2014;Singh and Kalamdhad 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nawab et al . found that native plant species can be used to recover soils that are contaminated by the accumulation of high concentrations of heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, significant correlation was found in agricultural products, Cd-Pb (r = 0.271), Cr-Cu (r = 0.525), Cd-Cu (r = 0.427) and Pb-Cu (r = 0.363) at the p<0.05 level, which were comparatively weaker than that in soils. This implies that these metals originate from the same polluting source or present multiple contamination to different degrees [53]. The significant correlation coefficients between heavy metals in soils and agricultural products assume that the source of heavy metal pollution in mining areas was anthropogenic (mining and smelting activities).…”
Section: Correlation Analysis Of Heavy Metal In Soils and Agriculturamentioning
confidence: 99%